'Robbed of one's eyes': Re-viewing the Holocaust. Issue 2 (1st October 2014) - Quigley, Paula
The literal and/or figurative violation of the human eye has been a striking figure of cinema since its inception, reflecting back on the act of spectatorship itself. Here, an uncanny confrontation between our role as spectators and how we 'see' history takes place directly through the eyes of a child.